Accreted ice mass ratio (k‐factor) for rotating wind turbine blade profile and circular cylinder. Issue 4 (21st December 2018) - Sokolov, Pavlo; Jin, Jia Yi; Virk, Muhammad S.
Abstract: This paper describes a study to investigate the relation between ice accretion on a rotating wind turbine blade profile (airfoil) and a reference collector (circular cylinder). This relation, known as " k ‐factor, " describes the ratio of accreted ice mass on a reference collector and wind turbine blade profile. Analyses are carried out by performing a series of multiphase numerical simulations and ISO 12494‐based analytical calculations. The results show that k ‐factor is not equal to constant 20, contrary to currently postulated assumption by VTT and can vary to a significant degree depending on a number of different operating and geometric parameters. These factors include the effects of blade geometry on ice accretion, droplet collision efficiency, droplet distribution spectrum, and median volume diameter under different ambient conditions pertaining to wind speed and tip speed ratios experienced by both the reference collector and wind turbine blade. The results presented in this paper provide a simplistic explanation about k‐ factor variance; however, further validation is necessary, in particular when it comes to the ice accretions on different wind turbine blade profiles under different operating and geometric conditions.